2006
DOI: 10.1080/00015458.2006.11679962
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Tumour of the Rectum: Laparoscopic Approach of a Rare Localization of GIST

Abstract: The authors present the case of a 60 year-old man known for a rectal polyp which was diagnosed in 1994 and since then followed-up by means of a colonoscopy associated with periodic biopsies. Recently, the results of a biopsy revealed positive markers for the diagnosis of Gastro-Intestinal Stromal Tumor (GIST). Despite the absence of malignant criteria, an anterior resection of the rectum was performed by laparoscopy and the patient rapidly recovered. Epidemiology, diagnosis and management of this rare location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…Yang Z et al reported that transnal surgery has a great bene t in rectal GISTs, including short operation time, less blood loss, quick revovery and low complication rate [16]. Several small scale case reports also indicate that transanal endoscopic and laparoscopic excision is safe and could be an alternative treatment of rectal GISTs [17][18][19]. However, there were no study report the comparision between minimally invasive surgery and open surgery in rectal GISTs.…”
Section: Discussionmentioning
confidence: 99%
“…Yang Z et al reported that transnal surgery has a great bene t in rectal GISTs, including short operation time, less blood loss, quick revovery and low complication rate [16]. Several small scale case reports also indicate that transanal endoscopic and laparoscopic excision is safe and could be an alternative treatment of rectal GISTs [17][18][19]. However, there were no study report the comparision between minimally invasive surgery and open surgery in rectal GISTs.…”
Section: Discussionmentioning
confidence: 99%
“…La protéine c-kit est un récepteur transmembranaire dont le ligand est un facteur de croissance. Dans les cellules exprimant le gène c-kit muté, l'activation non régulée de la protéine est à l'origine d'une prolifération cellulaire incontrôlable aboutissant à l'apparition d'une tumeur [1,[6][7][8].…”
Section: Discussionunclassified
“…D'autres signes peuvent être observés tels que les troubles du transit, les signes de compression, l'altération de l'état général, voire même une masse palpable [2,[6][7][8][9].…”
Section: Discussionunclassified